PERGESERAN HUKUM WARIS ADAT DI KALANGAN MASYARAKAT MELAYU DI KECAMATAN NONGSA PROPINSI KEPULAUAN RIAU - CONNY RIMAWATI (PREMISE LAW JURNAL, 2015)
The fisrt conclusion is that the shift of the principles of in heritance in Malay adat in Nongsa subdistrict can he seen from the fact that the heirs in Malay community in Nngsa subdistrict have the right to receive inheritance but the priority is for the members of nuclear family (husband, wife, children) unless the heir is still single and has no child, Inheritance distribution system which used to based on faraid law changes into the inheritance distribution using the way deliberation and concencus to seek justice that receive the sama amount. The second was that the factors influencing the development of inheritance law of Malay adat in Nongsa subdistrict Kepulauan Riau province werw the significant impact of modernization on kindship relation, Islamic law compilation and jurisprudence The third was that the role of adat institution in Nongsa Subdistrict, kepulauan Riau Province was more prioritized to settle the inheritance disputes rather than through the court of lawMeaning that family relationship in Nonsa subdistrict is still very strong and the advice of adat leader and the Islamic scholars is still used as guidance in settling the problems occurred, The adat institution also plays an important role in improving the brotherhood relationship that has been damaged by dispute. Keywords: Shift, Adat Inheritance, Malay Community, Nongsa Subdistrict